AQUATIC PHYSICAL THERAPY IN CEPHALIC EXTREMITY MUSCLE RELAXATION - Laura CHECHERIŢĂ (Romanian Dental Association for Education, 2014)
Muscular relaxation offers the possibility of muscular reconditioning by methods of aquatic physical kinetic therapy with the establishment of new neural-muscular engrams and, implicitly, of new patterns of mandible dynamics, the aim of this study being the study of different methods of treatment through physical factors, the assessment of action and efficiency, along with the integration of these methods within a treatment algorithm that will, finally, lead to stomatognatic system and cephalic musculature equilibrium.